Wi-Fi Protocol Vulnerability Discovery Based on Fuzzy Testing - Kunhua Zhu; Guohong Zhu (Institute of Advanced Engineering and Science, 2013)
To detect the wireless network equipment whether there is protocol vulnerability, using the method of modular design and implementation of a new suitable for Wi-Fi protocol vulnerability discovery fuzzy test framework. It can be independent of its transmission medium, produce deformity packet and implementation of the attack on the target system. The author firstly describes the wireless network protocol vulnerability discovery and fuzzy test in this paper，then focused on the test frame technical scheme, detailed technical realization and so on, and its application are analyzed. In the experimental stage the fuzzy test is applied to a wireless networks gateway, the test results show that the fuzzy test framework can be well applied to the wireless network equipment agreement loophole mining work. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3147